Gospoda-tovarishchi . Gospoda-tovarishchi . Gentlemen-Comrades . Господа-товарищи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of women's role in politics. Featured in the program: Lakhova, Ekaterina Filippovna (Leader of the Faction "Zhenshchiny Rossii" [Women of Russia]) Дискуссия о роли женщин в политике. В программе участвуют: Лахова, Екатерина Филипповна (Лидер фракции "Женщины России")